(Not) Looking Like A Refugee: Symbolic Borders of Habitus in Media Representations of Refugees. Issue 2 (3rd April 2022) - Kotilainen, Noora; Pellander, Saara
Abstract : Political debate about refugees is heavily influenced by how media images depict them. Centering on the victim/threat dichotomy in relation to the visual construction of the refugee figure, scholarship on media representations of refugees fails to acknowledge the historical layers of how refugees are visually conceptualized. Through scrutiny of historical Finnish media representations of refugees from the late 1930s through to contemporary discussions of asylum-seekers arriving in around 2015, the paper shows that images of refugees and the use of these in political debates go beyond the victim/threat dichotomy. We posit that perceptions as to 'deserving' and 'undeserving' refugees are linked to historically formed hierarchical notions of habitus and agency underpinned by racial and global-politics-connected motivations. Racialized and global political hierarchies in Western visual arrangements of picturing refugees can be conceptualized as symbolic borders of habitus.